Cholesterol effects on the tumor immune microenvironment: from fundamental concepts to mechanisms and implications - Lagunas-Rangel, Francisco Alejandro (Frontiers in Oncology, 2025)
In many cancers, the tumor microenvironment is enriched with cholesterol due to increased biosynthesis and uptake by cancer cells, resulting in the accumulation of cholesterol, cholesterol esters, oxysterols and other metabolites with various functions. These molecules serve as structural components, energy sources and intracellular signaling mediators, while their toxic by-products are secreted to suppress anti-tumor immune activity and prevent lipid peroxidation that could induce cancer cell apoptosis. Immune cells in the tumor microenvironment also contribute to cholesterol dynamics. Tumor-associated macrophages (TAMs) release cholesterol to support tumor cell metabolism, while myeloid-derived suppressor cells (MDSCs) also release cholesterol and consume essential metabolites such as L-arginine, which impairs T-cell proliferation and activation. Elevated cholesterol in dendritic cells impairs migration and tumor antigen presentation and, in lymphocytes, favors the development of a regulatory T cells (Treg) phenotype and inhibits the release of antitumor cytokines, further weakening the immune response. These findings suggest that targeting cholesterol metabolism is a promising strategy for cancer treatment, improving the efficacy of immune checkpoint blockade (ICB) therapies. In this manuscript, the molecular mechanisms underlying the effects of cholesterol on the tumor immune landscape are reviewed and the potential of cholesterol-lowering drugs to enhance antitumor immune responses is explored.